Subcutaneous progesterone (Prolutex)® for luteal phase support in cycles of in vitro fertilization–embryo transfer - A retrospective cohort study. Issue 4 (2020) - Hibshi, Ali; Aldriweesh, Amani; Saeed, Bahjat; Coskun, Serdar; Awartani, Khalid
No abstract available